Assessing potential of plastic waste management policies for territories sustainability: case study of Reunion Island. (2022) - Bénard, Fiona; Malet-Damour, Bruno
Abstract: The accumulation of plastic waste in nature and the oceans results from management policies that have not been able to find efficient and sustainable solutions. The circular economy is the basis of the current political will, willing to be the most virtuous. However, its implementation still seems conceptual, especially in the case of island territories. The work proposed in this paper assesses different waste management policy scenarios, screened against the global requirements of the Sustainable Development Goals (SDGs), the needs of the circular economy (CEs), and the challenges of local development (LCIs). The results highlight the lack of transversality of some policies as well as the inadequacy of their applicability or efficiency in an island environment. The importance of the diagnostic scale is pointed out, especially in elaborating territorial policies on waste management. The cross reading of the territory's needs and the potential of the nature of the waste, such as plastic, allowed to propose a new management plan wishing to answer the territorial challenges and stakes, such as those of Reunion Island.